Bronchitis In Children: Principles Of Modern Therapy (Eurasian Medical Research Periodical, 2024)
Bronchitis in children is diverse and is one of the most common diseases of the respiratory tract. The course of the disease can be either acute or chronic. Acute bronchitis (J20.0–J20.9), according to the modern classification, is acute inflammation of the bronchial mucosa without signs of damage to the lung tissue. Acute (simple) bronchitis (J20), as a rule, occurs against the background of an acute respiratory viral infection, which in 20% of patients is an independent cause of the disease. At the same time, 40–45% of patients have viral-bacterial associations. Among the viral pathogens, the most common are influenza, parainfluenza, adenoviruses, respiratory syncytial, corona and rhinovirus, ECHO and Coxsackie viruses. Among bacterial pathogens, Streptococcus pneumoniae, Haemophilus influenzae and Moraxella catarrhalis are currently the leaders